Queen of our times the life of Elizabeth II - Hardman, Robert 1965- (Macmillan, 2022)
The definitive new biography of Her Majesty The Queen by one of Britain's leading royal authorities. With original insights from those who know her best, unseen papers, new interviews with world leaders and a fresh perspective on the longest reign in British history, Robert Hardman tells the full life story of the most famous woman in the world. Like her father and grandfather before her, Elizabeth II was not born to be monarch. Yet she has reigned through more change than any sovereign since 1066. From her accession as a young mother of two in 1952 to the age of Covid-19, she has become a global phenomenon commanding unrivalled respect and affection. Elizabeth II: Her Life. Her Reign. Her Story follows the astonishing journey of the quietly determined young woman who has gone on to lead her family and her people through good times and bad for longer than most people have been alive. This is a must-read study of dynastic survival and renewal, spanning abdication, war, romance, danger, tragedy, drama, brickbats, laughter heroes and villains right up to the present day. Bestselling author Robert Hardman brings his long experience and expertise to this richly entertaining portrait of a world leader who remains as intriguing today as the morning she came to the Throne aged twenty-five